Hierarki Kebutuhan Maslow Pada Naskah Drama "Ayahku Pulang" Karya Usmar Ismail - Taufiq Hidayat; Akhmad Fatoni (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2025)
Literary works are expressions of the author's creativity that reflect the complexity of the author's life and the existing socio-cultural dynamics. Literary psychology functions to understand the psychological aspects contained in literary works, as well as how the author's background and experiences influence the process of creating the work. Drama as a performing art displays conflict, emotions, and interactions between characters that convey messages about social and cultural life. This study analyzes the drama "Ayahku Pulang" by Usmar Ismail, which raises emotional and social themes about the loss of a head of the family, and the psychological impact it has on family members. Abraham Maslow's psychological theory is used to analyze the psychological needs of the characters in this drama, focusing on the hierarchy of human needs, from physiological needs to achieving self-actualization. This study aims to provide insight into the relationship between psychology and literature and to enrich understanding of characters in literary works through a psychological approach.